Meningkatkan Kemampuan Operasional Matematika Siswa Kelas I Melalui Penggunaan Media Benda Konkret Siswa Kelas I MIN 1 Solok Selatan - Mitraturrahmi, Mitraturrahmi (Journal of Development Education and Learning (JODEL), 2025)
This Classroom Action Research aimed to enhance first-grade students’ mathematical operational skills through concrete objects as learning media. The study involved 17 students of MIN 1 Solok Selatan and applied the Kemmis and McTaggart model through two cycles of planning, action, observation, and reflection. Data were collected via formative tests, observations, worksheets, and documentation, and analyzed quantitatively and qualitatively. Results showed that concrete objects improved mastery of addition and subtraction, and fostered participation, creativity, and collaboration. The average formative test score increased from 52% to 68% in the first cycle and reached 85% in the second. Learning motivation, group engagement, and students’ ability to explain strategies also improved. It is concluded that concrete objects are an effective, engaging, and experiential strategy, recommended for consistent use in first-grade mathematics instruction.